The "model township" of Sharpeville: the absence of political action and organisation, 1960-1984. - Vally, Natasha Thandiwe (My University, 2011)
Sharpeville has become a seminal part of South African history and has captured the minds and memories of many, both nationally and globally. While much attention has been placed on the documentation of the events of the 21st of March 1960- the date of the Sharpeville massacre- surprisingly little has been recorded about the history of the township beyond this. This report aims to begin to fill the lacuna in this part of South African history by examining the reasons behind the dearth of political action and organisation in Sharpeville from its formation through to the early 1980s. The report examines Sharpeville as a ‘model township’, dissects what this concept means and begins to suggest how this conceptualisation affected political organising in the area. The report argues that Sharpeville as a ‘model township’ experienced political quiescence throughout the 1960s and 1970s which was only punctured by spontaneous political action. The report then goes on to explain and scrutinise the possible reasons for this quiescence
A research report submitted to the School of Social Sciences, Faculty of Humanities of the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Arts in History